Perspektif Tindakan Sosial Tenaga Kesejahteraan Sosial Kecamatan (TKSK) Dinas Sosial Kota Denpasar - Rudyanto, Gerald Timoty Untung; Nugroho, Wahyu Budi; Tamim, Imron Hadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the perspective of social actions taken by Social Welfare Workers at the sub-district level (TKSK) in the Social Service Office of Denpasar City. Using Max Weber’s theory of social action rationality, this research explores the meaning and motivations behind the social actions taken by TKSK in carrying out their duties. These social actions are performed to assist communities in need of social welfare services, both in terms of physical and emotional support. Through a qualitative approach, data were collected using in-depth interviews, direct observations, and documentation involving TKSK, the Head of the Denpasar City Social Service, as well as the community members receiving services from TKSK. The findings show that, despite working in challenging conditions, with minimal salaries and contracts that need to be renewed every year, they continue to perform their profession with full commitment. Their social action rationality is not only seen in terms of the benefits they receive but also in their social awareness and motivation to help others, as well as their dedication to reducing social disparities in society. This study provides insights into how TKSK manage their social responsibilities despite the challenging work conditions and minimal compensation.